Reliability and Safety Engineering for Safety-Critical Systems in Computer Science: A Study into the Mismatch between Higher Education and Employment in Brazil and India - Singh P.; Singh L.K. (My University, 2025)
Contribution: This article details a systematic study to investigate knowledge that graduate students have about reliability and safety engineering (RSE), comparing it with industry expectations. Background: Reliability and safety have always been the main focus while developing safety-critical systems (SCS). An interview study was conducted with engineering students in India and Brazil and with experienced practitioners to investigate a perceived mismatch between education and employment on knowledge related to RSE in SCS. Research Question: How does student knowledge of RSE for SCS compare with industry expectations? What measures could be taken by institutes and universities providing computer engineering courses to better meet the expectations of industries regarding SCS? Methodology: Interviews and discussions were conducted with 21 practitioners from ten different organizations to identify what expectations they hold for the students they recruit to develop SCS, as these SCS have high reliability and safety requirements. Interviews were conducted with graduate students of various engineering disciplines to assess their knowledge of RSE for SCS. Analyses were conducted to compare industry expectations with students' knowledge. Findings: Analyses indicated most graduate students do not have the range of knowledge regarding RSE that recruiters see as essential for the development of SCS. Hence, it is paramount to rethink computing curricula - to include RSE-related topics. © 1963-2012 IEEE.